Relative Localization Method of Multiple Micro Robots Based on Simple Sensors. (14th February 2013) - Mao, Ling; Chen, Jiapin; Li, Zhenbo; Zhang, Dawei
This paper presents a simple relative positioning algorithm for multiple micro robots. The micro robot is designed as a differential driven vehicle and actuated by MEMS-based electromagnetic micromotors. A simple relative positioning approach based only on one infrared emitter, receiver and compass is presented. Using this method, we characterized the accuracy of positioning between robots and identified sources of imprecision. Finally, this module is clearly demonstrated with the autonomous docking of multiple micro robots. The ability of our algorithm makes it cost effective and easy to deploy its application to multiple micro robots.